Diffusion of sulfur-containing compounds in petroleum residue fractions I. Hindered diffusion through polycarbonate membranes at ambient conditions. (1st November 2016) - Chen, Zhentao; Wu, Yun; Zheng, Mengyuan; Liu, Junfeng; Xu, Zhiming; Zhao, Suoqi; Xu, Chunming
Abstract: Hindered diffusion of sulfur-containing compounds in Venezuela atmospheric residue fractions through pore of polycarbonate membranes was investigated by using a diaphragm cell at 298 K. The results confirmed that residue fractions are all polydispersive mixtures. The sizes of membrane pore and fractions are the principal factors to diffusivities. In contrast to four fractions obtained by SFEF (supercritical fluid extraction and fraction) technique, there is a significant decrease in diffusion coefficients of maltenes and asphaltenes with increase of concentrations. Combining diffusivity variation of sulfur compounds in maltenes and asphaltenes with the study in literature, different aggregate degree was deduced for them over concentrations of 0.1–40 g/L. The influence of aggregation on diffusion coefficients enlarged as fractions become heavier and membrane pores become narrower. Hindered diffusion shows significant effect on transfer of residue fractions across membrane pores, especially for heavier fractions with higher concentrations diffusing through 15 nm membrane. Therefore, a number of large pores are required to provide sufficient channels for easy access of heavy components into active sites of catalyst. Comparisons between experimental results and theoretical prediction revealed that the actual hindered degree of sulfur-containing compounds in Venezuela residue fractions is more severe than that of predicted by the Renkin equation, which is due to the nonspherical structure of sulfide or thiophene derivatives.